The Effect of Using the Avanue Logan Problem Solving (Laps)-Heuristic Learning Model on Students' Mathematic Problem-Solving Ability SMP Muhammadiyah 1 Medan - Azis, Zinal; Fadillah, Jihan Husna (Lembaga Riset Mutiara Akbar, 2022)
The formulation of the problem in this study is Is there any effect of using the LAPS Heuristic model on the mathematical problem-solving ability of students in class VIII SMP Muhammadiyah 1 Medan on the subject of SPLDV. This study aims to determine whether there is an effect of the LAPS Heuristic model on the mathematical problem-solving ability of students in class VIII SMP Muhammadiyah 1 Medan on the subject of SPLDV. The instruments used in this study were tests and observations. The subjects in this study were class VIII- T2 which consisted of 30 students (as the experimental class) and class VIII-T3 which consisted of 30 students (as the control class). The object of this research is the ability to solve mathematical problems using the LAPS - Heuristic learning model. From the results of the study, it can be seen that using the LAPS – Heurtistic learning model has a positive effect on improving the mathematical abilities of eighth grade students of SMP Muhammadiyah 1 Medan T.P 2021/2022